A novel approach for tetrahedral-element-based finite element simulations of anisotropic hyperelastic intervertebral disc behavior - Fasser, Marie-Rosa; Kuravi, Ramachandra; Bulla, Marian; Snedeker, Jess G.; Farshad, Mazda; Widmer, Jonas (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral discs are microstructurally complex spinal tissues that add greatly to the flexibility and mechanical strength of the human spine. Attempting to provide an adjustable basis for capturing a wide range of mechanical characteristics and to better address known challenges of numerical modeling of the disc, we present a robust finite-element-based model formulation for spinal segments in a hyperelastic framework using tetrahedral elements. We evaluate the model stability and accuracy using numerical simulations, with particular attention to the degenerated intervertebral discs and their likely skewed and narrowed geometry. To this end, (i) annulus fibrosus is modeled as a fiber-reinforced Mooney-Rivlin type solid for numerical analysis. (ii) An adaptive state variable dependent explicit time step is proposed and utilized here as a computationally efficient alternative to theoretical estimates. (iii) Tetrahedral-element-based FE models for spinal segments under various loading conditions are evaluated for their use in robust numerical simulations. For flexion, extension, lateral bending, and axial rotation load cases, numerical simulations reveal that a suitable framework based on tetrahedral elements can provide greater stability and flexibility concerning geometrical meshing over commonly employed hexahedral-element-based ones for the representation and study of spinal segments in various stages of degeneration.